Penggunaan Kriptografi Klasik Enkripsi Deskripsi Menggunakan Metode Vignere Cipher Berbasis Website - Mazidah, Isti'anatul; Tahir, Muhlis; Soleha; Hamdani; Ramadhan, Yogi Rifansyah (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2024)
As time goes by, advances in technology also make it easier for people to communicate. One of the most common things to do is use computers to communicate, while computer networks are needed to transmit data or information. When collecting data, security and privacy are two very important aspects of data communication, whether for personal purposes or for group data security. One of the most effective ways to ensure data security and integrity is to use cryptographic techniques using the Vigenere Cipher method. Vigenere Cipher is a technique that can be used to encrypt text so that information cannot be read or misused by those who are not asked to receive the text. The aim of this research is to simplify the encryption process and description of the vigenere cipher method using websate. This research uses a literature study method based on various journals and experiments, including system implementation and design techniques. Test results on websites created using manual mapping show the same results. Both produce appropriate encryption and plaintext. Keywords: Vignere Cipher, Cryptography, Security